Urgensi DVI (Disaster Victim Identification) Di Lingkungan Militer - Purwanto Panji Sasongko (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Regulation of the Minister of Defense of the Republic of Indonesia Number 29 of 2014 concerning Standardization of Health Support in Disaster Management states that in order to provide optimal health support to prevent and minimize casualties and disability during disaster management operations within the Ministry of Defense and the Indonesian National Armed Forces, standardized health support is required from each health unit to ensure effective, efficient, and accountable implementation. Method: This paper uses normative juridical analysis supported by prescriptive methods related to the identification of mass disaster victims in the military, specifically regarding the organization and delivery of DVI services for mass casualties in the military. Results: The organization and delivery of DVI services for mass casualties in the military have not been implemented because Regulation of the Minister of Defense Number 29 of 2004 concerning Standardization of Health Support in Disaster Management within the Ministry of Defense and the Indonesian National Armed Forces only regulates the provision of optimal health support to prevent and minimize casualties and disability, while there are no regulations governing the identification of mass disaster victims, particularly deceased TNI soldiers. Conclusion: The Ministry of Defense and the TNI do not yet have a SOTK (Orgas Structure and Work Procedures) regarding DVI and there are no regulations governing Identification Efforts for soldiers who are victims of mass disasters. Keywords: Disaster Victim Identification, Military Environment, Mass Casualties ABSTRAK Peraturan Menteri Pertahanan Republik Indonesia Nomor 29 Tahun 2014 Tentang Standarisasi Dukungan Kesehatan Dalam Penanggulangan Bencana, yang menyatakan bahwa dalam rangka penyelenggaraan dukungan kesehatan yang optimal untuk mencegah dan meminimalisasi korban jiwa dan kecacatan pada operasi penanggulangan bencana di Lingkungan Kementerian Pertahanan dan Tentara Nasional Indonesia, diperlukan ketersediaan dukungan kesehatan yang standar dari masing-masing satuan kesehatan agar terlaksana secara efektif, efisien dan akuntabel. Metode: yang digunakan pada tulisan ilmiah ini adalah yuridis normatif didukung dengan preskriptif yang terkait dengan Identifikasi korban bencana yang bersifat massal di lingkungan militer, yaitu Bagaimana Organisasi dan Pelayanan DVI pada korban massal di lingkungan Militer. Hasil: Organisasi dan Pelayanan DVI pada korban massal di lingkungan militer belum dapat terwadahi oleh karena pada Permenhan No 29 tahun 2004 tentang Standarisasi dukungan Kesehatan dalam penanggulangan bencana di lingkungan Kemhan dan TNI hanya mengatur tentang penyelenggaraan dukungan kesehatan yang optimal untuk mencegah dan meminimalisasi korban jiwa dan kecacatan, sedangkan upaya identifikasi pada korban bencana massal khususnya pada prajurit TNI yang meninggal belum ada peraturan yang mengaturnya.Kesimpulan: Secara Umum, Kemhan dan TNI belum mempunyai SOTK (struktur Orgas dan Tata Kerja) mengenai DVI dan belum ada peraturan yang mengatur tentang Upaya Identifikasi bagi prajurit korban bencana massal. Kata Kunci: Disaster Victim Identification, Lingkungan Militer, Korban Massal